Double Maximum Ratios of Viruses to Bacteria in the Water Column: Implications for Different Regulating Mechanisms - He, Lei; Yin, Kedong; Yuan, Xiangcheng (Frontiers in Microbiology, 2019)
The viruses play an important role in limiting bacterial abundance in oceans and hence regulating bacterial biogeochemical functions. A cruise was conducted in September 2005 along a transect in the deep South China Sea. The results showed the double maxima in the ratio of viral to bacterial abundance (VBR) in the water column: a deep maximum at 800-1000 m coinciding with the oxygen minimum zone (OMZ) and a subsurface maximum at 50-100 m near the subsurface chlorophyll maximum (SCM) layer. At the deep maximum of VBR, both viral and bacterial abundances were lower than those in the upper layer, but the former was reduced less than the latter. In contrast, at the subsurface maximum of VBR, both viral and bacterial abundances increased to the maximum, with viral abundance increasing more than bacterial abundance. The results suggest that two VBR maxima were formed due to different mechanisms. In the SCM, the VBR maximum is due to an abundant supply of organic matter, which increases bacterial growth, and stimulates viral abundance faster. In contrast, in the OMZ, organic matter is consumed and limits bacterial growth, but viruses are less limited by organic matter and continue to infect bacteria, leading to the maximum VBR. The OMZ in the deep water column of oceans is over hundreds of years old and receives a constant supply of organic matter from the water above. However, the oxygen level cannot be depleted to anoxia. Bacterial respiration is largely responsible for oxygen consumption in the OMZ; and hence, any process that limits bacterial abundance and respiration contributes to the variation in the OMZ. Viral control of bacterial abundance can be a potential mechanism responsible for slowing down oxygen consumption to anoxia in the OMZ. Our finding provides preliminary evidence that viruses are an important player in controlling bacterial abundance when bacterial growth is limited by organic matter and thus regulate the decomposition of organic matter, oxygen consumption and nutrient re-mineralization in deep oceans.